2009
DOI: 10.1001/archdermatol.2009.540
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Ocular Complications of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis

Abstract: To describe the acute and late ocular manifestations of toxic epidermal necrosis (TEN), Stevens-Johnson syndrome (SJS), and overlap syndrome and to identify predictors for the development of ocular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 37 publications
7
114
1
Order By: Relevance
“…4 Amongst survivors, long-term ocular complications can be serious and are thought to affect approximately 60% of patients. 6 Corneal damage in the form of scarring or limbal stem cell failure is the most severe ocular outcome.Conjunctival scarring can contribute to longterm corneal pathology and subsequent visual impairment.For example, palpebral conjunctival scarring can cause chronic micro-trauma with the blink reflex, while symblepharon formation can lead to poor tear film dynamics and predisposition to severe dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…4 Amongst survivors, long-term ocular complications can be serious and are thought to affect approximately 60% of patients. 6 Corneal damage in the form of scarring or limbal stem cell failure is the most severe ocular outcome.Conjunctival scarring can contribute to longterm corneal pathology and subsequent visual impairment.For example, palpebral conjunctival scarring can cause chronic micro-trauma with the blink reflex, while symblepharon formation can lead to poor tear film dynamics and predisposition to severe dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from ONIAM showed that files of 13 dead patients reached the end of CCI/ONIAM procedures and compensation was proposed for 8 of these patients (25% of all accepted files). Although the diseases are now managed by multidisciplinary teams, long-term sequelae with severe functional impairment may still be underestimated [4] and could explain why some records were refused because of insufficient disability (9/23 = 39% of refusals). Sequelae might be perhaps better estimated if dermatologists were always included in expert committees.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that the mortality of these severe cutaneous adverse reactions (SCARs) to drugs is 23% 6 weeks and 34% 1 year after the acute phase [3]. Long-term psychological and physical sequelae may occur, especially mucosal and ocular scars that may induce severe visual impairment or even blindness [4,5]. Thus, many patients report altered quality of life [6].…”
Section: Introductionmentioning
confidence: 99%
“…The failed case had immune dysregulation, which persisted after surgery, leading to the recurrence. 26 Therefore further studies are necessary to improve the management of preoperative and postoperative inflammation in patients with autoimmune disease.…”
Section: The Surgical Goals Of Treating Symblepharon Arementioning
confidence: 99%